INFLUENCE OF ACARICIDAL HERBAL DRUGS ON CELLULAR COMPOSITION OF THE HEMOLYMPH OF BEES - Лукьянова, Г. А.; Перебийнис, А. В. (Scientific Progress & Innovations, 2013)
The effect of various herbal acaricides (herb wormwood, eucalyptus leaves, smoke of horseradish root) on the body the bees, namely the cellular composition of hemolymph is studied. Treatment with the use of smoke of roots of horse-radish renders a positive effect on normalization of cellular composition of hemolymph. An amount of enicytoides and platocytoides in the hemolymph of bees of the family, infested by varroatisic ticks, practically corresponded to the physiological indexes after treatment. Acaricides treatment with the use of grass of wormwood and leaves of eucalyptus also had a positive effect, however it was weaker. The best effect on normalization of haemolymphogramma of bees was rendered by treatment with smoke of roots of horse-radish.